EPIPHYTIC ALGAE ON THE MOSS COMMUNITY OF GRIMMIA LAWIANA AROUND SYOWA STATION, ANTARCTICA (Ninth Symposium on Polar Biology) - オオタニ, シュウジ; カンダ, ヒロシ; OHTANI, Shuji; KANDA, Hiroshi (National Institute of Polar Research, 1987)
P(論文) The epiphytic algae on the moss community of Grimmia lawiana around Syowa Station were taxonomically and ecologically investigated. Based on the moss samples from the Prince Olav Coast, the S6ya Coast and the Sor Rondane Mountains, East Antarctica, 19 species of blue-green algae, dominated by Nostoc sp. and Stigonema minutum and a single diatom species were recognized. Among the nine localities of moss colonies, Strandnibba and S0r Rondane Mountains were considered to have more favorable habitats for the presence of epiphytic algae. The prominent algal flora on the moss colonies might be caused by the abundant water supply from the continental glacier during the summer season and by the rich nutrients from the excrement of resting sea birds. departmental bulletin paper